The English national cohort study of flooding and health: cross-sectional analysis of mental health outcomes at year one. (December 2017) - Waite, Thomas; Chaintarli, Katerina; Beck, Charles; Bone, Angie; Amlôt, Richard; Kovats, Sari; Reacher, Mark; Armstrong, Ben; Leonardi, Giovanni; Rubin, G.; Oliver, Isabel
Abstract Background In winter 2013/14 there was widespread flooding in England. Previous studies have described an increased prevalence of psychological morbidity six months after flooding. Disruption to essential services may increase morbidity however there have been no studies examining whether those experiencing disruption but not directly flooded are affected. The National Study of Flooding and Health was established in order to investigate the longer-term impact of flooding and related disruptions on mental health and wellbeing. Methods In year one we conducted a cross sectional analysis of people living in neighbourhoods affected by flooding between 1 December 2013 and 31 March 2014. 8761 households were invited to participate. Participants were categorised according to exposure as flooded, disrupted by flooding or unaffected. We used validated instruments to screen for probable psychological morbidity, the Patient Health Questionnaire (PHQ 2), Generalised Anxiety Disorder scale (GAD-2) and Post Traumatic Stress Disorder (PTSD) checklist (PCL-6). We calculated prevalence and odds ratios for each outcome by exposure group relative to unaffected participants, adjusting for confounders. Results 2126 people (23%) responded. The prevalence of psychological morbidity was elevated amongst flooded participants ([n  = 622] depression 20.1%, anxiety 28.3%, PTSD 36.2%) and disrupted participants ([n  = 1099] depression 9.6%, anxiety 10.7% PTSD 15.2%). Flooding was associated with higher odds of all outcomes (adjusted odds ratios (aORs), 95% CIs for depression 5.91 (3.91–10.99), anxiety 6.50 (3.77–11.24), PTSD 7.19 (4.33–11.93)). Flooded participants who reported domestic utilities disruption had higher odds of all outcomes than other flooded participants, (aORs, depression 6.19 (3.30–11.59), anxiety 6.64 (3.84–11.48), PTSD 7.27 (4.39–12.03) aORs without such disruption, depression, 3.14 (1.17–8.39), anxiety 3.45 (1.45–8.22), PTSD 2.90 (1.25–6.73)). Increased floodwater depth was significantly associated with higher odds of each outcome. Disruption without flooding was associated with borderline higher odds of anxiety (aOR 1.61 (0.94–2.77)) and higher odds of PTSD 2.06 (1.27–3.35)) compared with unaffected participants. Disruption to health/social care and work/education was also associated with higher odds of psychological morbidity. Conclusions This study provides an insight into the impact of flooding on mental health, suggesting that the impacts of flooding are large, prolonged and extend beyond just those whose homes are flooded.